Elections during COVID-19: Welcome clarifications, unanswered questions - FUN, Joel Wei Xuan (Institutional Knowledge at Singapore Management University, 2021)
On 10th July 2020, Singapore held its Parliamentary Elections, while in the midst of the COVID-19 pandemic. Elections have been similarly held elsewhere during this pandemic, and suffice to say that the pandemic, and its resulting implications, have raised various interesting legal questions in some of these jurisdictions.1 To that end, a wide range of regulations and rules pertaining to elections have also been passed in response to the COVID-19 pandemic. In some jurisdictions, such as certain states in the United States, voting by mail was allowed with no excuse required, so as to prevent the further spread of COVID19 via the polling stations. In others, lockdown restrictions were completely eased to facilitate voting, to the extent that some voters were also allowed to choose whether to wear protective devices or not (e.g., gloves and masks)